2007
DOI: 10.1289/ehp.10194
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating the Developmental Neurotoxicity of Chlorpyrifos: A Mechanisms-Based Approach in PC12 Cells

Abstract: BackgroundOrganophosphate developmental neurotoxicity involves multiple mechanisms converging on neural cell replication and differentiation.ObjectivesWe evaluated mechanisms contributing to the adverse effects of chlorpyrifos (CPF) on DNA synthesis, cell number and size, and cell signaling mediated by adenylyl cyclase (AC) in PC12 cells, a neuronotypic cell line that recapitulates the essential features of developing mammalian neurons.ResultsIn undifferentiated cells, cholinergic receptor antagonists had litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 61 publications
(150 reference statements)
6
45
1
Order By: Relevance
“…Indeed, we previously found that nicotine can protect neuronotypic cells in culture from the direct antimitotic and oxidative effects of chlorpyrifos (Qiao et al, 2003, 2005; Slotkin et al, 2007a). Nevertheless, using the same in vivo treatment model as in the present study, we found that prolonged prenatal nicotine exposure actually worsened the impact of chlorpyrifos on the development of cholinergic synaptic function (Slotkin and Seidler, 2015), reflecting the fact that nicotine itself is a developmental neurotoxicant (Slotkin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously found that nicotine can protect neuronotypic cells in culture from the direct antimitotic and oxidative effects of chlorpyrifos (Qiao et al, 2003, 2005; Slotkin et al, 2007a). Nevertheless, using the same in vivo treatment model as in the present study, we found that prolonged prenatal nicotine exposure actually worsened the impact of chlorpyrifos on the development of cholinergic synaptic function (Slotkin and Seidler, 2015), reflecting the fact that nicotine itself is a developmental neurotoxicant (Slotkin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this series of experiments, mecamylamine and atropine (nicotinic and muscarinic acetylcholine receptor antagonists, respectively) were coincubated with CPF and CPO, and the effects on axonal transport and mitochondrial dynamics were assessed. The concentrations of mecamylamine and atropine were based on previously published neuronal culture studies (Heppner and Fiekers, 1992;Slotkin et al, 2007;Ueda et al, 2008).…”
Section: Cpf/cpo-related Inhibition Of Ache Is Not Necessarily Responmentioning
confidence: 99%
“…However, toxicity has been reported at doses that do not inhibit AChE [14,15] . Therefore, other mechanisms including the induction of oxidative stress have been implicated in CPF-induced toxicity [16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%